A coastal reservoir of biodiversity for Upper Pleistocene human populations: palaeoecological investigations in Gorham's Cave (Gibraltar) in the context of the Iberian Peninsula (Quaternary Science Reviews, 2008)
Palaeobotanical (pollen, charcoal) data from Gorham’s Cave reveals a diversified landscape in the Gibraltar region during the Middle (c. 32 560–23 780 year BP) and Upper Palaeolithic (c. 18 440–10 880 BP). Inferred vegetation types include oak, pine, juniper, and mixed woodlands and savannahs, grasslands with heaths, heliophytic matorrals, phreatophytic formations (e.g. riverine forests, wetlands), and thermomediterranean coastal scrub. A revision of palaeoecological data suggests that patches of trees persisted even in northern and continental territories of the Iberian Peninsula during the cold stages of OIS3 and OIS2. However, a southern Mediterranean coastal shelf extending from Gibraltar to Málaga, and probably further north up to Murcia, was unique in its combination of thermo-, meso-, and supramediterranean plant and animal species. Given the composition of these assemblages, this shelf and its adjacent mountains represented a crucial reservoir of biodiversity during the Upper Pleistocene. It is within this physiographically complex context with its diversity of resources where the last Neanderthals extraordinarily survived until c. 24 000 BP, that is over 10 000 years later than the disappearance of Neanderthals from elsewhere in temperate Europe.